Modulating the tumor immune microenvironment with locoregional image-guided interventions - Jain, Samagra; Sheth, Rahul A. (Frontiers in Immunology, 2023)
Cancer immunotherapy has gained significant attention in recent years and has revolutionized the modern approach to cancer therapy. However, cancer immunotherapy is still limited in its full potential due to various tumor immune-avoidance behaviors and delivery barriers, and this is seen in the low objective response rates of most cancers to immunotherapy. A novel approach to immunotherapy utilizes image-guided administration of immunotherapeutic agents directly into a tumor site; this technique offers several advantages, including avoidance of potent toxicity, bypassing the tumor immunosuppressive microenvironment, and higher therapeutic bioavailability relative to systemic drug administration. This review presents the biological rationale for locoregional image-guided immunotherapy administration, summarizes the existing interventional oncology approaches to immunotherapy, and discusses emerging technological advances in biomaterials and drug delivery that could further advance the field of interventional oncology.